2015
DOI: 10.1002/cphc.201402703
|View full text |Cite
|
Sign up to set email alerts
|

A Reevaluation of the Photolytic Properties of 2‐Hydroxybenzophenone‐Based UV Sunscreens: Are Chemical Sunscreens Inoffensive?

Abstract: The excited states of a set of popular sunscreen agents (2-hydroxybenzophenone, oxybenzone, and sulisobenzone) are studied by using femto- and nanosecond time-resolved spectroscopy. Upon excitation, the compounds undergo an ultrafast excited-state intramolecular proton transfer (ESIPT) reaction as the major energy-wasting process and the rate constant of this reaction is k=2×10(12) s(-1) . The ESIPT yields a keto conformer that undergoes a fast, picosecond internal conversion decay. However, a photodegradative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 19 publications
3
69
1
Order By: Relevance
“…The conclusion of these calculations and subsequent analysis points to the likely photoproduct being a long-lived keto-isomer which has undergone significant excess rotation about the aliphatic C−C bond, referred to as a trans keto-isomer, vide infra. Similar studies have also observed the generation of a photoproduct and have attributed it to the formation of a phenoxyl radical after O−H bond fission 26 . Thus TVAS measurements have not only complemented TEAS measurements, where the timescales of identified processes are in very good agreement, each has provided something unique.…”
Section: Transient Vibrational Absorptionsupporting
confidence: 60%
See 1 more Smart Citation
“…The conclusion of these calculations and subsequent analysis points to the likely photoproduct being a long-lived keto-isomer which has undergone significant excess rotation about the aliphatic C−C bond, referred to as a trans keto-isomer, vide infra. Similar studies have also observed the generation of a photoproduct and have attributed it to the formation of a phenoxyl radical after O−H bond fission 26 . Thus TVAS measurements have not only complemented TEAS measurements, where the timescales of identified processes are in very good agreement, each has provided something unique.…”
Section: Transient Vibrational Absorptionsupporting
confidence: 60%
“…Oxybenzone has been shown to be an effective sunscreen with respect to its ability in absorbing UVR across the UV-A and UV-B regions dissipating it on ultrafast timescales 24;25 . Contrary to this, oxybenzone has been suggested to form a potentially adverse photoproduct after being excited by UVR 26 . Furthermore, there is evidence to suggest that oxybenzone may behave as an endocrine disrupter and a photoallergen 23;27 .…”
Section: Artificial Photoprotection: Sunscreensmentioning
confidence: 99%
“…(ii ) Formation of a long-lived photoproduct, most likely through extended C−C bond rotation forming a non-chelated, trans keto tautomer as previously reported [16]. However, a possibility remains that the photoproduct might be a phenoxyl radical [18]. The first of these routes appears dominant, given that the majority of the GSB recovers on the time scale of the experiment; the incomplete recovery is therefore attributed to the formation of a photoproduct which does not recover by the maximum time delay available of 2 ns (selected transients are given in the SI).…”
Section: Discussionmentioning
confidence: 72%
“…Organic filters are typically aromatic molecules which absorb UVR and dissipate it through ultrafast pathways. Examples include avobenzone [14,15], oxybenzone [16][17][18][19] and octocrylene [20]. Inorganic scatterers, in addition to absorption, also operate by scattering UV radiation away.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation